KONDISI SOSIAL PENYAIR DALAM TEKS SYAIR 1999 KARYA ACHMAD MATHAR (KAJIAN STRATA NORMA ROMAN INGARDEN) - Ikhti Nur Halimah, Afnan Arummi (Arabic Literature Department, 2019)
This research discusses the text structure and social condition of the poet in poetry “1999” by Achmad Mathar. The purpose of this research is to outline and to describe the text structure, and the social condition of the poet in that poetry. This research uses qualitative-descriptive method by elaborating of data text that contains words, phrases, or verses. The data were analyzed using the theory of strata Roman Ingarden norm and theory of solipsism. The result shows that the text structure in the poetry ”1999” by Achmad Mathar has five layers, namely the sound layer, the meaning layer, layer of things, the world layer, and metaphysical layer. The five layers of strata give rise to the impression of reading and provide in-depth meaning which can arouse the spirit of fighting to achieve independence. As for the social conditions of the poet expressed through two interrelated phenomenasof the poet. The phenomenons namely: Saddam Hussein's life story and cartoon Hanzhala by Nājī al-'Alī. Both have lofty ideals for freeing the Middle East from the influence of the West and its allies importances.